Impact of extra-articular pathologies on groin pain: An arthroscopic evaluation. - Mitsunori Kaya (PLoS ONE, 2018)
For patients who have anterior hip pain evaluated by Patrick's test and tenderness at Scarpa's triangle, we perform periarticular debridement based on the hypothesis that extra-articular pathologies are responsible for the hip pain. The purpose of this study was to categorize the endoscopic extra-articular findings and to evaluate the clinical significance of periarticular pathologies in anterior hip pain.Arthroscopic findings of 77 patients who underwent periarthritic debridement were evaluated. As extra-articular pathologies, injuries of the direct head and reflective head of the rectus femoris muscle were evaluated. A thin layer of fat tissue normally exists on the anterior inferior iliac spine (AIIS), the attachment site of the direct head of the rectus femoris muscle. The macroscopic appearance of the fat pad on the AIIS was categorized as normal, blood vessel-rich adipose tissue or adipose tissue with fibrosis or scar formation and histologically confirmed. Adhesion of gluteal muscles to the joint capsule was also evaluated.Of the 77 patients, 75 had rupture of the direct head of the rectus femoris. In contrast, rupture of the reflective head was extremely rare. Seven patients had a normal fat pad on the AIIS, 11 had blood vessel-rich adipose tissue and 55 had adipose tissue with fibrosis. Fat tissue was completely replaced by fibrous scar tissue in another 4 patients. In 64 patients, adhesion between the anterior joint capsule and gluteus muscles was marked. Groin pain disappeared soon after the operation even when labral tears were not repaired and all patients returned to daily life and sports activities within 2 weeks after operation.Rectus femoris tendinosis, fibrosis of the AIIS fat pad, and adhesion of gluteal and rectus femoris muscles are common extra-articular pathologies in patients with anterior hip pain. Management of only these lesions induces rapid relief of anterior hip pain even in the absence of labral tear repair. My observations suggest that it is desirable to be aware of the presence of periarticular pathologies as a cause of groin pain.